Phosphorus in brown soils of mountain pastures in Uzbekistan - Akhatov , A.; Buriev, S. S.; Nurmatova, V. B. (AgroChemistry and Soil Science, 2022)
The aim of this work is to assess the content and distribution of phosphorus in the profile of brown soils (Cambisols, Kastanozems, Leptosols) of the mountain pastures of the Republic of Uzbekistan. Soil incisions laid 7 agricultural areas of the country. Field research, sampling and analytical work were performed in 2019–2021. The list of indicators under study includes the degree of soil erodation, the general content of humus, the content of the clay fraction, the general content of phosphorus and the content of the movable phosphorus in the selected clay fraction and in the soil. A detailed division of phosphorus into reserves and their calculation according to the methodology of calculations of reserves of nutrition elements according to N.I. Gorbunov (1978). The studied mountain brown soils are characterized by a loamy granulometric composition, nutty-cloddy structure, a slightly acidic or slightly alkaline reaction. The total humus content in the upper horizon varies from 1.0 to 6.8 %. The proportion of the clay fraction is from 2.9 to 18.3 %. The content of phosphorus in the clay fractions is 2–3 times higher than in the soil as a whole and the maximum is 0.558 %. The phosphorus reserves was allocated – close, immediate and potential. Fluctuations in the content of phosphorus reserves in the humus horizon were revealed: immediate from 6 to 26 %, near - from 7 to 19 %, potential, dominant in the total content of 68 to 80%. In the humus horizon, an insoluble form of phosphorus occurs, which increases the resistance of soils to water erosion due to the formation of water resistance structures. Uneven distribution of phosphorus and its reserves in brown soils on the mountain pastures of Uzbekistan, both in the soil profile and the regions of the country, is stated, which is affected by the relief, exposure of slopes, the features of soil -forming rocks, atmospheric precipitation, hydrothermal conditions, and the period of biological activity of soils. The losses of the near and direct reserves of the humus lead to a decrease in the total content of the phosphorus as a whole.